Probing Ultra-Hot Jupiters with CRIRES+: Atmospheric retrievals from phase-resolved emission spectroscopy - Ramkumar, Swaetha (Trinity College Dublin. School of Physics. Discipline of Physics, 2026)
The discovery of planets orbiting other stars—exoplanets—has transformed our understanding of planetary systems, revealing a diversity of worlds far beyond the Solar System. Among these, hot Jupiters and their hotter counterparts, the ultra-hot Jupiters, provide unique laboratories for prob- ing atmospheric physics and chemistry under extreme conditions for which there are no Solar System analogues. Their short orbital periods and bright host stars make them especially favourable targets for atmospheric characterisation. Recent advances in ground-based high-resolution spectroscopy have enabled the atmospheres of these planets to be probed in unprecedented detail. In particular, the recently upgraded CRyogenic high-resolution InfraRed Echelle Spectrograph (CRIRES+) at the Very Large Telescope (VLT) has opened a new window onto thermal emission in the near-infrared. At the same time, new statistical frameworks have provided a pathway for extracting quantitative constraints on atmospheric structure and composition. Within this context, this thesis investigates the chemical and thermal properties of ultra-hot Jupiter atmospheres using high-resolution emission spectroscopy, assessing both the feasibility of these emerging methodologies and the capabilities of CRIRES+ for this type of science. The first study focused on the ultra-hot Jupiter MASCARA-1b. Pre-eclipse observations revealed strong emission signatures of both refractory and volatile species, demonstrating that current ground-based NIR instruments can probe these species simultaneously. Retrievals further constrained the vertical temperature structure, chemical abundances, and the atmospheric carbon-to-oxygen ratio (C/O). These findings also highlighted the importance of chemically consistent modelling for robust interpretation of ultra- hot Jupiter atmospheres. The second study presented post-eclipse observations of the same planet, obtained two years after the pre-eclipse data. These provided a complementary view of the day-side atmosphere and enabled a phase-resolved emission spectroscopy analysis of MASCARA-1b at high resolution. Molecular emission signatures were detected in both datasets, consistently indicating a thermal inversion. Retrievals constrained the temperature-pressure profile, chemical abundances, and elemental ratios, with results broadly consistent across both datasets and in agreement with solar C/O values. The consistency of these findings indicates no significant temporal or spatial variability in the atmosphere of MASCARA-1b over the observed two-year baseline. The final study extended the analysis to a mini-survey of four ultra-hot Jupiters observed in thermal emission with CRIRES+. Cross-correlation analysis revealed new detections of refractory species alongside confirmations of previously detected volatiles. Atmospheric retrievals were conducted for WASP-121b and WASP-189b, providing quantitative constraints on their chemical compositions. While robust detections of species and thermal inversions were recovered, the inferred elemental ratios varied across retrieval frameworks, datasets and assumed thermal structures. These results underscore both the capability of CRIRES+ emission spectroscopy to probe refractory and volatile species in ultra-hot Jupiter atmospheres and the present limitations of one-dimensional retrievals for reliably constraining their elemental abundances. Overall, the studies presented in this thesis demonstrate the feasibility of combining CRIRES+ emission spectroscopy with advanced retrieval techniques to probe the chemical composition, thermal structure and dynamics of ultra-hot Jupiter atmospheres. Future work building on this thesis will refine these methods and extend them to larger samples, improving our understanding of these extreme planetary systems.
APPROVED
Keywords: Ultra-Hot Jupiters; CRIRES+; Exoplanets; Atmospheric retrievals; High-resolution spectroscopy